2007
DOI: 10.1089/end.2007.9905
|View full text |Cite
|
Sign up to set email alerts
|

Prior Video Game Exposure Does Not Enhance Robotic Surgical Performance

Abstract: In the extremes of video-game experience tested in this study, game playing was inversely correlated with the ability to learn robotic suturing. This study suggests that advanced surgical skills such as robotic suturing may be learned more quickly by athletes and musicians. Prior extensive video-game exposure had a negative impact on robotic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 12 publications
3
32
1
1
Order By: Relevance
“…As a result, surgical simulators are widely used to enable trainees to acquire as much technical competence as possible outside the operating room. Recent interest has focused on whether video-gaming might be a useful adjunct [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…As a result, surgical simulators are widely used to enable trainees to acquire as much technical competence as possible outside the operating room. Recent interest has focused on whether video-gaming might be a useful adjunct [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…On the other hand, laparoscopic, non-surgical predictors may have no meaning in robotic surgery. In that sense, previous literature showed that prior extensive video game exposure had a negative impact on robotic performance (15). Therefore, robotic characteristics (mainly 3D vision and ambidexterity) might distinguish the two methods in terms of nonsurgical predictors.…”
Section: Discussionmentioning
confidence: 95%
“…Con ello disminuye el tiempo quirúrgico y se reducen las complicaciones (19): los cirujanos sin experiencia en este tipo de técnicas tienen tasas más altas de complicaciones operatorias por procedimiento (20), aunque cabe señalar que no se ha establecido la equivalencia en horas de entrenamiento con simuladores virtuales o pelvitrainer a cirugía en vivo (21,22). La literatura mundial ha confirmado que las habilidades quirúr-gicas endoscópicas son mejores en cirujanos que previamente hubieran jugado video juegos (principalmente los de deportes) y aquellos que utilizan instrumentos musicales (23). También se ha referido que no existe diferencia estadísticamente significativa entre hombres y mujeres residentes que utilizaron simuladores de realidad virtual en térmi-nos de error o de la economía del movimiento (24).…”
Section: Discussionunclassified